Achievement of a healthy and prosperous village for Modelomo Village and Mohungo Village in Boalemo Regency as part of the Village Sustainable Development Goals (SDGs) - Asri Silvana Naiu; Nikmawatisusanti Yusuf (Fisheries and Society, 2021)
SDGs (Suistainable Development Goals) Village is an integrated effort to realize village without poverty, hunger, village that care about health, village that grow evenly, village that care about the environment, village that care about education, women-friendly village, networked village, culturally responsive village to accelerate the achievement of the Sustainable Development Goals. The achievement of an environmental care village in Modelomo Village is motivated by the condition of the village environment which is far from clean, and concern for reaching a health care village in Mohungo Village by seeing the number of stunting cases which is quite high. These two villages are neighbors and are located in Tilamuta District, Boalemo Regency. The community service activities were carried out by the Village Development Program KKN undergraduate students, each of which amounted to 15 people for each village, which was carried out in mid-September to early November 2021. The method used is to provide education about the importance of environmental cleanliness for oneself and environmental comfort, invite the community to dredge garbage and mud, build waterways, initiate the creation of a waste bank, make organic and non-organic waste bins and propose a plan to procure a waste fleet to the Modelomo village government. In Mohungo Village, besides students providing education through outreach to the village community, especially pregnant women and those with toddlers, they also build healthy kitchens to process healthy and nutritious food